2020
DOI: 10.3390/ma13071563
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure Influence of SACX0307-TiO2 Composite Solder Joints on Thermal Properties of Power LED Assemblies

Abstract: The effect of the microstructure of solder joints on the thermal properties of power LEDs is investigated. Solder joints were prepared with different solder pastes, namely 99Sn0.3Ag0.7Cu (as reference solder) and reinforced 99Sn0.3Ag0.7Cu–TiO2 (composite solder). TiO2 ceramic was used at 1 wt.% and with two different primary particle sizes, which were 20 nm (nano) and 200 nm (submicron). The thermal resistance, the electric thermal resistance, and the luminous efficiency of the power LED assemblies were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…In the assembly of power LEDs, a soldering process is typically used. As previously shown [17,24,25], the composition of the soldering alloy, the type of reflow oven, and the soldering temperature profile in time can influence thermal resistance of a soldering joint between the case of a power LED and the PCB.…”
Section: Introductionmentioning
confidence: 86%
“…In the assembly of power LEDs, a soldering process is typically used. As previously shown [17,24,25], the composition of the soldering alloy, the type of reflow oven, and the soldering temperature profile in time can influence thermal resistance of a soldering joint between the case of a power LED and the PCB.…”
Section: Introductionmentioning
confidence: 86%
“…Thermal and optical parameters of the LED assemblies were also measured: real thermal resistance (R th ), electric thermal resistance (R the ), and luminous efficiency (η F ). A custom-designed LED test system was used to measure the diodes' DC current-voltage characteristics, as described by Skwarek et al [32]. Both the thermal and optical parameters of LEDs were measured simultaneously.…”
Section: Evaluation Methodsmentioning
confidence: 99%
“…TiO 2 . As was proved by Skwarek et al, the addition of TiO 2 to the soldering paste influences the thermal properties of LEDs (Skwarek et al, 2020). It was shown that using soldering paste SACX0307-TiO 2 , it is possible to obtain visibly better thermal properties of soldering joints than using classical paste SACX0307.…”
Section: Introductionmentioning
confidence: 93%
“…The thermal properties of all the layers that ensure heat flow between these elements of the heat flow path are also essential. In particular, solder joints between the device examined and the printed circuit board can affect the efficiency of heat transfer as well (Skwarek et al, 2020;Illés and Hars anyi, 2008).…”
Section: Introductionmentioning
confidence: 99%